Skip to main content

Final Review

Classifying Formulas#

  1. PPQQ((PQ)¬(PQ))((P\wedge Q)\rightarrow \neg (P\vee Q))
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}
    This formula is contingent. The formula is true in rows 2, 3, 4; and false in row 1.
  2. PPQQRR(((PQ)R)(P(QR)))(((P\wedge Q)\rightarrow R)\leftrightarrow (P\rightarrow (Q\rightarrow R)))
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    3. T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    4. T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    5. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    6. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    7. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    8. F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    This formula is a tautology. The fromula is true in every row of the truth table.
  3. PPQQ((PQ)P)((P\vee Q)\rightarrow P)
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}
    3. F\mathsf{F}T\mathsf{T}F\mathsf{F}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}
    This formula is contingent. The formula is true in rows 1, 2, 4; and false in row 3.
  4. PPQQ((PQ)(QP))((P\rightarrow Q)\vee (Q\rightarrow P))
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}
    This formula is a tautology. The fromula is true in every row of the truth table.
  5. PPQQ(¬(PQ)P)(\neg (P\rightarrow Q)\rightarrow P)
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}
    This formula is a tautology. The fromula is true in every row of the truth table.
  6. PPQQRR((PQ)((PR)Q))((P\rightarrow Q)\rightarrow ((P\wedge R)\rightarrow Q))
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    3. T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    4. T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    5. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    6. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    7. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    8. F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    This formula is a tautology. The fromula is true in every row of the truth table.
  7. PPQQ(¬P(PQ))(\neg P\rightarrow (P\rightarrow Q))
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}
    This formula is a tautology. The fromula is true in every row of the truth table.
  8. PP¬(P¬P)\neg (P\vee \neg P)
    1. T\mathsf{T}F\mathsf{F}
    2. F\mathsf{F}F\mathsf{F}
    This formula is a contradiction. The formula is false in every row of the truth table.
  9. PPQQ¬(P(PQ))\neg (P\vee (P\wedge Q))
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}
    2. T\mathsf{T}F\mathsf{F}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}
    This formula is contingent. The formula is true in rows 3, 4; and false in rows 1, 2.
  10. PP(P¬P)(P\leftrightarrow \neg P)
    1. T\mathsf{T}F\mathsf{F}
    2. F\mathsf{F}F\mathsf{F}
    This formula is a contradiction. The formula is false in every row of the truth table.

Classifying Two Formulas#

  1. PPQQ(¬P¬Q)(\neg P\vee \neg Q)(PQ)(P\wedge Q)
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    These formulas are contradictory. The formulas have different truth values in every row of the truth table.
  2. PPQQ(P¬Q)(P\wedge \neg Q)¬(PQ)\neg (P\wedge Q)
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    3. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    These formulas are satisfiable. Both formulas are true in row 2.
  3. PPQQ¬(PQ)\neg (P\wedge Q)(¬P¬Q)(\neg P\wedge \neg Q)
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    These formulas are satisfiable. Both formulas are true in row 4.
  4. PPQQ¬(¬PQ)\neg (\neg P\vee Q)(P¬Q)(P\wedge \neg Q)
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    3. F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    4. F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    These formulas are tautologically equivalent. The fromulas have the same truth value in every row of the truth table.
  5. PPQQ¬(¬PQ)\neg (\neg P\vee Q)(PQ)(P\rightarrow Q)
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    These formulas are contradictory. The formulas have different truth values in every row of the truth table.
  6. PPQQ(PQ)(P\rightarrow Q)(¬PQ)(\neg P\vee Q)
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    These formulas are tautologically equivalent. The fromulas have the same truth value in every row of the truth table.
  7. PPQQ(PQ)(P\rightarrow Q)(QP)(Q\rightarrow P)
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    These formulas are satisfiable. Both formulas are true in rows 1, 4.
  8. PPQQ(P(Q¬Q))(P\rightarrow (Q\wedge \neg Q))¬P\neg P
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    2. T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    These formulas are tautologically equivalent. The fromulas have the same truth value in every row of the truth table.
  9. PPQQ(PQ)(P\leftrightarrow Q)(PQ)(P\wedge Q)
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    These formulas are satisfiable. Both formulas are true in row 1.
  10. PPQQRR(P(QR))(P\rightarrow (Q\vee R))((PQ)R)((P\vee Q)\rightarrow R)
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    3. T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    4. T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    5. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    6. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    7. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    8. F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    These formulas are satisfiable. Both formulas are true in rows 1, 3, 5, 7, 8.

Validity#

  1. AABBCC(AB)(A\rightarrow B)(AC)(A\rightarrow C)(A(BC))(A\rightarrow (B\wedge C))
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    3. T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    4. T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    5. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    6. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    7. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    8. F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    The argument is valid. The premises are all true in rows 1, 5, 6, 7, and 8. The conclusion is true in each of these rows.
  2. AABB¬(AB)\neg (A\vee B)¬A\neg A
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    2. T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    The argument is valid. The premises are all true in row 4. The conclusion is true in this row.
  3. AABB¬(AB)\neg (A\wedge B)¬A\neg A
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    2. T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    The argument is not valid. The premises are all true and the conclusion is false in row 2.
  4. AABBCC(AB)(A\rightarrow B)(BC)(B\rightarrow C)(AC)(A\rightarrow C)
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    3. T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    4. T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    5. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    6. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    7. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    8. F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    The argument is valid. The premises are all true in rows 1, 5, 7, and 8. The conclusion is true in each of these rows.
  5. PPQQ(PQ)(P\rightarrow Q)(¬PQ)(\neg P\rightarrow Q)QQ
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    The argument is valid. The premises are all true in rows 1 and 3. The conclusion is true in each of these rows.
  6. PPQQRR(PQ)(P\vee Q)¬(PR)\neg (P\vee R)(RQ)(R\rightarrow Q)¬R\neg R
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    2. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    3. T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    4. T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    5. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    6. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    7. F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    8. F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    The argument is valid. The premises are all true in row 6. The conclusion is true in this row.
  7. PPQQRR(PQ)(P\vee Q)(PR)(P\rightarrow R)(Q¬R)(Q\rightarrow \neg R)¬Q\neg Q
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    2. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    3. T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    4. T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    5. F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    6. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}F\mathsf{F}
    7. F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    8. F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    The argument is not valid. The premises are all true and the conclusion is false in row 6.
  8. PPQQ¬(PQ)\neg (P\vee Q)(¬QP)(\neg Q\rightarrow P)
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    2. T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    3. F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    4. F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    The argument is not valid. The premises are all true and the conclusion is false in row 4.
  9. PPQQRR¬(PQ)\neg (P\vee Q)PPRR
    1. T\mathsf{T}T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    2. T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    3. T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    4. T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    5. F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    6. F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    7. F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    8. F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    The argument is valid. There is no row in which all the premises are true. So, the argument is valid since there are no rows in which all the premises are true and the conclusion is false.
  10. PPRR(P¬P)(P\wedge \neg P)(R¬R)(R\wedge \neg R)
    1. T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    2. T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    3. F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    4. F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    The argument is valid. There is no row in which all the premises are true. So, the argument is valid since there are no rows in which all the premises are true and the conclusion is false.

Calculating (Conditional) Probabilities#

  1. PPQQRR(PR)(P\leftrightarrow R)QQ
    0.2 T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    0.1 T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    0.1 T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}
    0.2 T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    0.1 F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    0.1 F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    Pr(PR)Pr(P\leftrightarrow R) = \ =\ 0.500.50
    Pr(QPr(Q) = \ =\ 0.500.50
  2. PPQQRR((PR)Q)((P\wedge R)\rightarrow Q)
    0.2 T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    0.1 T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    0.1 T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    0.2 T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    0.1 F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    0.1 F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    0.1 F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    0.1 F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    Pr((PR)Q)Pr((P\wedge R)\rightarrow Q) = \ =\ 0.900.90
  3. PPQQRR(P¬Q)(P\rightarrow \neg Q)RR
    0.2 T\mathsf{T}T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    0.1 T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    0.1 T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    0.2 T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    0.1 F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    0.1 F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    0.1 F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    0.1 F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    Pr(P¬Q)Pr(P\rightarrow \neg Q) = \ =\ 0.700.70
    Pr(RPr(R) = \ =\ 0.500.50
  4. PPQQRR(Q(PR))(Q\wedge (P\wedge R))(PR)(P\wedge R)
    0.2 T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    0.1 T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    0.1 T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    0.2 T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    Pr(Q(PR)) = Pr(Q\mid (P\wedge R))\ =\ Pr(Q(PR))Pr(Q\wedge (P\wedge R))/ / Pr(PR)Pr(P\wedge R)  = \ =\ 0.200.20/ / 0.300.30 = 0.667\ =\ 0.667
  5. PPQQRR((PQ)R)((P\wedge Q)\wedge R)
    0.2 T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    0.1 T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    0.1 T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    0.2 T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}
    0.1 F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}
    0.1 F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    Pr((PQ)R) = Pr((P\wedge Q)\mid R)\ =\ Pr((PQ)R)Pr((P\wedge Q)\wedge R)/ / Pr(R)Pr(R)  = \ =\ 0.200.20/ / 0.500.50 = 0.400\ =\ 0.400
  6. PPQQRRPP((RQ)¬Q)((R\rightarrow Q)\wedge \neg Q)¬Q\neg Q
    0.2 T\mathsf{T}T\mathsf{T}T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    0.1 T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}
    0.1 T\mathsf{T}F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}T\mathsf{T}
    0.2 T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}T\mathsf{T}
    0.1 F\mathsf{F}T\mathsf{T}T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}
    0.1 F\mathsf{F}F\mathsf{F}T\mathsf{T}F\mathsf{F}F\mathsf{F}T\mathsf{T}
    0.1 F\mathsf{F}F\mathsf{F}F\mathsf{F}F\mathsf{F}T\mathsf{T}T\mathsf{T}
    Pr(PPr(P) = \ =\ 0.600.60
    Pr((RQ)¬Q) = Pr((R\rightarrow Q)\mid \neg Q)\ =\ Pr((RQ)¬Q)Pr((R\rightarrow Q)\wedge \neg Q)/ / Pr(¬Q)Pr(\neg Q)  = \ =\ 0.300.30/ / 0.500.50 = 0.600\ =\ 0.600